2022
DOI: 10.21037/qims-2021-07
|View full text |Cite
|
Sign up to set email alerts
|

‘Healthier Chinese spine’: an update of osteoporotic fractures in men (MrOS) and in women (MsOS) Hong Kong spine radiograph studies

Abstract: For the MrOS (Hong Kong) and MsOS (Hong Kong) baseline (BL) studies, community-dwelling 2,000 Chinese men (mean age: 72.3 years) and 2,000 Chinese women (mean age: 72.5 years) were recruited from 2001 to 2003. These two studies have spanned two decades till now. This review summarizes our spine radiograph results. Senile and post-menopausal osteoporosis were associated with intervertebral disc volume reduction; and in women, menopause accelerates disc degeneration. Elderly women's osteoporotic vertebral fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 77 publications
3
18
0
Order By: Relevance
“…This has led to some practical difficulties. For example, osteoporotic hip fracture prevalence among Chinese is generally no more than half that of Caucasians (6,56), and we demonstrated that both radiographic OVF and clinical OVF follow the same trend with their prevalences among Chinese being no more than half of those among Caucasians (6,7,36). However, earlier studies reported that OVF among East Asians is as prevalent as that of Caucasians (57,58).…”
Section: A B a Bsupporting
confidence: 55%
See 1 more Smart Citation
“…This has led to some practical difficulties. For example, osteoporotic hip fracture prevalence among Chinese is generally no more than half that of Caucasians (6,56), and we demonstrated that both radiographic OVF and clinical OVF follow the same trend with their prevalences among Chinese being no more than half of those among Caucasians (6,7,36). However, earlier studies reported that OVF among East Asians is as prevalent as that of Caucasians (57,58).…”
Section: A B a Bsupporting
confidence: 55%
“…This itself suggests that ECF negative OVD is already an osteoporotic phenomenon distinct from those vertebrae without OVD. We consider positive ECF as an additional sign of OVF, and a positive ECF sign would increase the confidence for OVF diagnosis, but ECF is not an essential sign of OVF (36).…”
Section: Critiques For Algorithm-based Qualitative (Abq) Criteriamentioning
confidence: 99%
“…Recent evidence suggests that, compared with Caucasians, the relative prevalence of osteoporotic vertebral fracture (OVF) follows the same pattern as other clinical fractures, with both radiographic and clinical OVF prevalences among older Chinese being no more than half of those of older Caucasians [Figures S1,S2 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)]. However, till now this conclusion heavily depends on the data from MrOS(Hong Kong) and MsOS(Hong Kong) studies.…”
Section: Ethical Statementmentioning
confidence: 99%
“…It has recently been shown that older Hong Kong Chinese women have a much lower prevalence and severity of osteoporotic vertebral fracture (OVF) than age-matched Rome Caucasian women (1)(2)(3). In one study, we compared spine radiographs (T4-L5) from two epidemiological studies conducted in Hong Kong [MsOS(Hong Kong) n=200] and in Rome (Roman Osteoporosis Prevention Project, n=200, age-matched subjects with both mean age: 74.1 years and range: 65-87 years).…”
mentioning
confidence: 99%
“…The Chinese subjects were from the MsOS(Hong Kong) study, which was an epidemiological research to study bone health among community dwelling Hong Kong Chinese women aged ≥65 years. The recruitment plan was designed so that the participants would represent the general elderly population in Hong Kong (3). At baseline all Hong Kong subjects were required to be able to walk without assistance, without bilateral hip replacement, and have the potential to survive the duration of primary study for at least 4 years as judged by their pre-existing medical status.…”
mentioning
confidence: 99%